2008
DOI: 10.1021/ol800099a
|View full text |Cite
|
Sign up to set email alerts
|

SmI2-Promoted Reformatsky-Type Coupling Reactions in Exceptionally Hindered Contexts

Abstract: Highly substituted, very hindered enones were synthesized using a two-step procedure that utilizes a diiodosamarium-promoted Reformatsky-type coupling and dehydration using Martin sulfurane. Both α-chloro-and α-bromoketones were coupled with a variety of carbonyl nucleophiles to form the intermediate β-hydroxyketones, occurring with excellent diastereoselectivity, favoring the syn isomer (R 1 = Me). This technique complements other methods and enables the preparation of enones outside of the scope of current o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 25 publications
(21 reference statements)
1
19
0
Order By: Relevance
“…Given the repeated failure encountered in these attempts, it was gratifying to note that a-bromoketone 15, which was obtained by treatment of ethyl ketone 14 with phenyltrimethyl ammonium tribromide (PTAB), [22] underwent a reductive Reformatsky-type [23] coupling with aldehyde 3. As nicely precedented by the work of Jamison et al, [14] SmI 2 was found to be an excellent reductant for this step. It is noteworthy that a-bromoketone 15, which-in contrast to the tert-alkyl substrates studied by Jamison et al [14c] -contains a sensitive stereogenic center at the second a-position, reacted smoothly and afforded the desired product 16 in up to 81 % yield.…”
Section: Resultssupporting
confidence: 65%
See 3 more Smart Citations
“…Given the repeated failure encountered in these attempts, it was gratifying to note that a-bromoketone 15, which was obtained by treatment of ethyl ketone 14 with phenyltrimethyl ammonium tribromide (PTAB), [22] underwent a reductive Reformatsky-type [23] coupling with aldehyde 3. As nicely precedented by the work of Jamison et al, [14] SmI 2 was found to be an excellent reductant for this step. It is noteworthy that a-bromoketone 15, which-in contrast to the tert-alkyl substrates studied by Jamison et al [14c] -contains a sensitive stereogenic center at the second a-position, reacted smoothly and afforded the desired product 16 in up to 81 % yield.…”
Section: Resultssupporting
confidence: 65%
“…It was found that 1chloroethyl magnesium chloride nicely serves this purpose and a general method was established, with which aldehydes can be converted into the respective a-chloroethyl ketones. As previously shown by Jamison et al, [14] the latter compounds are in turn capable to undergo a reductive SmI 2 -promoted coupling reaction with aldehydes to provide after dehydration the respective E-configured a,b-unsaturated ketones. When applied to compounds 3 and 4 a successful assembly was possible to an intermediate which was further converted into the title compounds upon reduction at C7 and macrolactamization.…”
Section: Introductionmentioning
confidence: 55%
See 2 more Smart Citations
“…tertButyl ethyl ketone was prepared following the reported procedure. [15] All reactions were monitored by thin-layer chromatography (TLC) with Haiyang GF254 silica gel plates. Flash column chromatography was carried out using 100-200 mesh silica gel at increased pressure.…”
Section: Methodsmentioning
confidence: 99%